A hazai területfejlesztési források foglalkoztatási támogatásainak vizsgálata Somogy megyében - Tóth, Erika (Acta Scientiarum Socialium, 2013)
The examination of domestic occupational subsidies from the funds of regional development in Somogy county There are remarkable developmental differences in Hungarian regions which are derived from ecological, social and economic origin. The development funds coming from the EU are not able to provide sufficient opportunities to solve each problems, so the intervention of the Hungarian funds are needed in order to maintain the development. To achieve this, certain methods of area-development have been introduced and some of these enable us to increase the rate of employment. In order to decrease the rate of unemployment in the current economical situation, our essential task is to support job creation and job retention. In this study I examined the awarded funds for work-motivation, as well as the payment obligations originating from employment in the period between 1996 and 2011, so as to certify the usefulness of the investments by the Hungarian state. The basis of this examination was the minimum-principle: the calculations have been made by assuming the employees’ salary as a minimum wage and the contributions that have to be paid as the smallest possible amount. The number of the employees for the time of the obligations was determined in monthly divisions using accumulated value coming from different estimates, so it was possible to take the notice of the annual and midyear changes of the payment obligation. It was verified during the examination of the rates and taxes as well as the financial support of the employees and the employers, that the subsidies totally returned and a certain amount of „profit” was also presented for the budget. Neither any incomes originating from increasing production, nor the reduction of budget expenditure, that is established by the job creation is considered in the study, so it is possible to estimate that the income gained directly from the employment covers the amount of subsidies.
Keywords: regional development; employment; financial support; obligations